Gestión de talento humano en el centro operativo local SIS ECU 911 Babahoyo - Zambrano Bustamante, Lilibeth Carolina (2021)
This case study is based on the Human Talent Management in the Local Operational Center SIS Ecu911 of the Babahoyo canton is a coordinating body that aims to respond to emergency calls presented by citizens with the implementation of a telecommunication system and a video surveillance equipment that allows the community to connect directly with the institution. It has a very good organizational structure and complies with the appropriate processes; The main problem that we have been able to identify is related to the lack of commitment and work materials on the part of the public institutions integrated into the security system and the poor external communication of users when reporting emergencies has increased the degree of dissatisfaction and poor job performance with the human talent of the Operational part of the company. The methodology that will be used in this research work will be under the qualitative method, with it we can implement techniques that lead us to clear, true and transparent results with the tests that we will use, which are interviews and surveys, which will allow us to investigate further. fund the situation that is happening in the areas of human talent validating the different criteria they have. Another technique that we have used is the documentary since all the information transcribed in the work are supported by the different readings of books, scientific journals and bibliographic sources.